Kemampuan Belanja Modal Memoderasi Pengaruh PAD, DAU, DAK dan SiLPA pada IPM - Wahyu, I Putu Adita; Dwirandra, A.A.N.B (E-Jurnal Akuntansi, 2015)
Independent variables such as PAD, DAU, DAK, and SiLPA allegedly not always have linear effect to HDI, due to contingent factors that influence the relationship. One of the contingency factor is capital expenditure . This study has pupose to determine the effect of PAD, DAU, DAK, and SiLPA on HDI, as well as the effect of PAD, DAU, DAK, and SiLPA with moderation of capital expenditure on HDI. Research includes eight districts and one city of Bali in a span of observations from 2008 to 2013. The location of this study, namely the Provincial Finance Bureau Office of Bali and the Bali Provincial Statistics. The test results showed PAD, DAK, and SiLPA have positive and significant effect on HDI while DAU has no effect on HDI in the District / City in Bali Province . Moderating variables (capital expenditure ) capable of moderating variable DAU, DAK, and SiLPA but not able to moderate variable PAD on HDI.
Keywords: PAD, DAU, DAK SiLPA, Capital Expenditure, HDI